Social Intelligence As A Predictor Of Competencies Among Prospective Counselors In Public Universities - Omogbai, Edith Omorionmwen; Jesuorobo, Wellington Omosefe (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The study investigated social intelligence as a predictor of counseling competencies among prospective counselors in public universities in Edo and Delta States. Its aim was to precisely examine the level of social intelligence among these individuals and determine whether it predicts their counseling competencies. Survey research design using the correlational approach was implemented in the study. The population of the study comprised all Master’s students in public universities in Edo and Delta who had completed the practical counseling course. A sample of 81 prospective counselors was used for the study. The researchers used the Tromsꝋ Social Intelligence Scale (TSIS) and the Counselor Competency Scale (CCS) as research instruments. Data analyses were carried out using descriptive statistics (mean and standard deviation) and regression analysis. The findings of the study implied the social intelligence level of future counselors was high, and social intelligence significantly predicted counseling competencies of prospective counselors (F=8.021, p< 0.01, R2=0.09).